Increased α2δ‐1–NMDA receptor coupling potentiates glutamatergic input to spinal dorsal horn neurons in chemotherapy‐induced neuropathic pain. Issue 2 (21st December 2018) - Chen, Youfang; Chen, Shao‐Rui; Chen, Hong; Zhang, Jixiang; Pan, Hui‐Lin
Abstract: Painful peripheral neuropathy is a severe and difficult‐to‐treat neurological complication associated with cancer chemotherapy. Although chemotherapeutic drugs such as paclitaxel are known to cause tonic activation of presynaptic NMDA receptors (NMDARs) to potentiate nociceptive input, the molecular mechanism involved in this effect is unclear. α2δ‐1, commonly known as a voltage‐activated calcium channel subunit, is a newly discovered NMDAR‐interacting protein and plays a critical role in NMDAR‐mediated synaptic plasticity. Here we show that paclitaxel treatment in rats increases the α2δ‐1 expression level in the dorsal root ganglion and spinal cord and the mRNA levels of GluN1, GluN2A, and GluN2B in the spinal cord. Paclitaxel treatment also potentiates the α2δ‐1–NMDAR interaction and synaptic trafficking in the spinal cord. Strikingly, inhibiting α2δ‐1 trafficking with pregabalin, disrupting the α2δ‐1–NMDAR interaction with an α2δ‐1 C‐terminus–interfering peptide, or α2δ‐1 genetic ablation fully reverses paclitaxel treatment‐induced presynaptic NMDAR‐mediated glutamate release from primary afferent terminals to spinal dorsal horn neurons. In addition, intrathecal injection of pregabalin or α2δ‐1 C‐terminus–interfering peptide and α2δ‐1 knockout in mice markedly attenuate paclitaxel‐induced pain hypersensitivity. Our findings indicate that α2δ‐1 is required for paclitaxel‐induced tonic activation of presynaptic NMDARs at the spinal cord level. Targeting α2δ‐1–bound NMDARs, not the physiological α2δ‐1–free NMDARs, may be a new strategy for treating chemotherapy‐induced neuropathic pain. Open science badges: This article has received a badge for *Open Materials * because it provided all relevant information to reproduce the study in the manuscript. The complete Open Science Disclosure form for this article can be found at the end of the article. More information about the Open Practices badges can be found athttps://cos.io/our-services/open-science-badges/ . Abstract : Although NMDA receptors are expressed presynaptically in the spinal dorsal horn, they are not bound to α2δ‐1 proteins and are in a quiescent state under the normal condition. Treatment with paclitaxel increases the expression of α2δ‐1 in primary sensory neurons and the interaction between α2δ‐1 and NMDA receptors, which promote the synaptic trafficking of α2δ‐1–bound NMDA receptor complexes and lead to presynaptic NMDA receptor hyperactivity in the spinal dorsal horn. The increased presynaptic NMDA receptor activity results in sustained potentiation in glutamate release to spinal dorsal horn neurons, which constitutes a critical mechanism of chemotherapy‐induced chronic pain. Open Science: This manuscript was awarded with the Open Materials Badge. For more information see:https://cos.io/our-services/open-science-badges/